Van der Waals epitaxial MOCVD-growth of (BixSb1−x)2Te3 (0 < x < 1) films. (28th July 2015) - Bendt, G; Sonntag, J; Lorke, A; Assenmacher, W; Hagemann, U; Schulz, S
Abstract: Epitaxial (Bi x Sb1− x )2 Te3 films with (0 <  x  < 1) were grown by the metal-organic chemical vapour deposition (MOCVD) process at 400 °C using the tailor-made precursors Et2 Te2, i -Pr3 Sb and Et3 Bi. The films grown on Al2 O3 (0001) substrates show a very smooth surface morphology as shown by a scanning electron microscope (SEM), atomic force microscopy (AFM) and transmission electron microscopy (TEM), while those grown on Si(100) are rather polycrystalline. The chemical composition of the crystalline films (x-ray powder diffraction (XRD)) was investigated by energy-dispersive x-ray (EDX) and x-ray photoelectron spectroscopy (XPS), and the in-plane transport properties were measured, and a strong dependency from the bismuth content was found, which allows the tuning of the carrier concentration and mobility in a wide range.